Role of cholescintigraphy with single-photon emission computerized tomography-computed tomography in detecting bronchobiliary fistula: Unusual complication of a common disease - Ravina, Mudalsha; Mishra, Ajit; Rajan, Abishek; Kumar, Narvesh; Kumar, Ashok; Gambhir, Sanjay (World Journal of Nuclear Medicine, 2018)
Bronchobiliary fistula (BFF) is an abnormal communication between the biliary tree and airway. A patient usually presents with cough and bilioptysis, and at times, it poses diagnostic and therapeutic challenge. This case demonstrates the usefulness of cholescintigraphy with single-photon emission computerized tomography in diagnosing BFF in case of hydatid cyst of the liver.
Keywords: Bronchobiliary fistula; single-photon emission computerized tomography-computed tomography; scintigraphy; technetium-99m N-(3-bromo-2; 4; 6-trimethylacetanilide)iminodiacetic acid